The Development of Mathematics E-Module Based on Problem Based Learning using Flip PDF Professional - Fuziani, Meilidya; Wafiqoh, Risnina; Agustine, Putri Cahyani (Universitas PGRI Sumatera Barat, 2025)
This research is motivated by the limitations of teachers who have not implemented teaching materials in schools, the lack of mathematics word problems related to everyday life issues, and using conventional methods in class resulting in low students' problem-solving abilities. This study was conducted to determine the characteristics of mathematics e-modules based on problem-based learning using the flip pdf professional application on valid and practical Matrix and to determine its potential effects. This research is a research and development with a 4D (four D) development model consisting of four stages, they are Define, Design, Develop, and Disseminate. This study develops a mathematics e-module based on problem-based learning using the flip pdf professional application on valid matrix with an average validity score of 98.89% including the criteria of